2013
DOI: 10.3171/2013.4.spine12719
|View full text |Cite
|
Sign up to set email alerts
|

Operating room radiation exposure in cone beam computed tomography–based, image-guided spinal surgery

Abstract: Object Surgeon and operating room (OR) staff radiation exposure during spinal surgery is a concern, especially with the increasing use of multiplanar fluoroscopy in minimally invasive spinal surgery procedures. Cone beam computed tomography (cbCT)–based, 3D image guidance does not involve the use of active fluoroscopy during instrumentation placement and therefore decreases radiation exposure for the surgeon and OR staff during spinal fusion procedures. However, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…14 However, our experience suggests that perhaps a larger volume of approximately [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] cases is required to demonstrate breach rates similar to those commonly reported in the literature. To our knowledge, the present report is the largest singlecenter series of thoracolumbar PSs placed using the O-arm and the first in the literature to quantify the learning curve for screw accuracy associ ated with this technology.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…14 However, our experience suggests that perhaps a larger volume of approximately [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] cases is required to demonstrate breach rates similar to those commonly reported in the literature. To our knowledge, the present report is the largest singlecenter series of thoracolumbar PSs placed using the O-arm and the first in the literature to quantify the learning curve for screw accuracy associ ated with this technology.…”
Section: Discussionmentioning
confidence: 79%
“…Computed tomography-based IGSS offers several advantages to the spine surgeon including greater accu racy of pedicle screw placement, 4,6,21,[24][25][26][27] minimal to no radiation exposure, 12,15,21,22 and potentially a short regis tration time. 5,[12][13][14] As with any new technology, CT-guid ed spinal surgery is prone to growing pains, which may force novice surgeons to abandon this technology early.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown improved accuracy for pedicle screw placement in spine surgery when using navigation [12][13][14] . In addition, it avoids RE to the surgeon [9,10,14,15] Surgeons have voiced concerns about the radiation dose they receive over a career of spine surgery. The cumulative RE places the surgeon at risk for the development of malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of thyroid cancer in spine surgeons was almost 40 times greater than the general population according to the Scoliosis Research Society Morbidity and Mortality Committee [16] . Navigation is one tool that may decrease this risk, with prior studies reporting navigation generating "0" or undetectable RE to surgeon and OR staff [9,17,18] . Despite the use of navigation greatly improving the accuracy in screw placement in spine surgery, there is still debate regarding the RE to patients by O-arm [18,19] The O-arm delivers a different dose of radiation, which ranged from 6 mGy to 66 mGy depending on the settings of the machine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation